A Novel PWM Inverter Topology for Intuitive Motion Controls of EV With BLDC Motor - Pramanik, Ranjan; Pradhan, Jatin Kumar; Pati, Bibhuti Bhusan (International Journal of Integrated Engineering, 2024)
Permanent magnet brushless DC (PMBLDC) motors are having a huge impact on next-generation electric vehicle (EV) applications due to their high-performance accuracy and reliability in the motion control area. This paper offers a unique inverter switching method to control the PMBLDC motor for high voltage (HV) e-mobility applications. In this work, the speed of a permanent BLDC motor is controlled by a suitable inverter switching selections via inverter mapped with motor position. Hence, the anticipated switching method is depended on identifying the sector position and selecting the suitable control logic for switching inverter. Here, a feedback and feedforward loop design based control logic are used for tracking and improved input-output performance, respectively. The feedback loop used a proportional-integral-derivative (PID) controller. The gains of the PID controller are tuned by using dominant pole placement technique to ensure robust loop performance. Further, a feed forward gain is designed to improve the input output performance. Simulations are carried out with a developed hardware set-up of BLDC motor with AKD interface device to validate the system performances experimentally.